2008
DOI: 10.1309/uuh2xheckevd45pf
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Mistakes and Deferrals in the Frozen Section Diagnosis of Bronchioloalveolar Carcinoma and Well-Differentiated Pulmonary Adenocarcinoma

Abstract: The frozen section diagnosis of lung nodules is difficult because inflammatory atypia and histologic artifacts can simulate a malignancy. From a total of 2,405 frozen sections examined, 143 cases were misdiagnosed or deferred, including 65 with reactive atypia (RA) and 35 bronchioloalveolar carcinomas or well-differentiated adenocarcinomas (BAC-AC), resulting in deferral and error rates of 4.36% and 1.58%, respectively. The presence of 25 pathologic features was evaluated by using an evidence-based pathology (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Most papers specifically dealing with frozen section analysis of lung lesions f2 cm originate from Japan. In a review by GUPTA et al [41] including nodules examined over a 5-yr period, the error rate was 1.6% and deferral rate 4.4%. In the other papers summarised in table 3, predictive value ranged from 93% to 100%, but not all studies clearly mention accuracy of frozen section analysis.…”
Section: Intraoperative Frozen Section Analysis Diagnostic Accuracymentioning
confidence: 97%
See 1 more Smart Citation
“…Most papers specifically dealing with frozen section analysis of lung lesions f2 cm originate from Japan. In a review by GUPTA et al [41] including nodules examined over a 5-yr period, the error rate was 1.6% and deferral rate 4.4%. In the other papers summarised in table 3, predictive value ranged from 93% to 100%, but not all studies clearly mention accuracy of frozen section analysis.…”
Section: Intraoperative Frozen Section Analysis Diagnostic Accuracymentioning
confidence: 97%
“…Few articles deal with the exact procedure of intraoperative frozen section examination and its accuracy. These are summarised in table 3 [36][37][38][39][40][41][42][43][44][45][46][47][48]. Most papers specifically dealing with frozen section analysis of lung lesions f2 cm originate from Japan.…”
Section: Intraoperative Frozen Section Analysis Diagnostic Accuracymentioning
confidence: 99%
“…Problems in the frozen section diagnosis of lung lesions have previously been investigated in our laboratory [5][6][7] and by others. 15 In a review of frozen sections performed on 183 small (,1.5 cm) lung nodules, Marchevsky et al 5 concluded that the distinction between bronchioloalveolar carcinoma (currently adenocarcinoma in situ) and atypical adenomatous hyperplasia was often problematic, and that the diagnostic accuracy was lowest for small (,1.1 cm) lesions.…”
Section: Clinical Impact Of Frozen Section Errors and Deferralsmentioning
confidence: 99%
“…15 In a review of frozen sections performed on 183 small (,1.5 cm) lung nodules, Marchevsky et al 5 concluded that the distinction between bronchioloalveolar carcinoma (currently adenocarcinoma in situ) and atypical adenomatous hyperplasia was often problematic, and that the diagnostic accuracy was lowest for small (,1.1 cm) lesions. In a subsequent study, Gupta et al 6 used an evidence-based approach to identify 5 features (multiple growth patterns, anisocytosis, atypia involving .75% of the lesion, macronucleoli, and atypical mitoses) that were most useful in distinguishing bronchioloalveolar carcinoma-well differentiated adenocarcinoma from reactive atypia in frozen sections. In their study, bronchioloalveolar carcinoma-well differentiated adenocarcinoma was considered the same diagnosis, and the problem was to distinguish these lesions from reactive atypia.…”
Section: Clinical Impact Of Frozen Section Errors and Deferralsmentioning
confidence: 99%
See 1 more Smart Citation